Copyright Protection Of Digital Content On Services Over The Top (Ott) In Indonesia On The Spotify Music Streaming Platform - Sabina, Riyana; Safiranita, Tasya (UNIVERSITAS PAKUAN, 2025)
Over-The-Top (OTT) services like Spotify have transformed the way digital content is consumed in Indonesia, highlighting the urgent need for effective copyright protection. This study evaluates the effectiveness of copyright protection for digital content on OTT platforms, focusing on Spotify's policies and their alignment with Law No. 28 of 2014 on Copyright . The research questions addressed include the effectiveness of copyright protection for digital content on OTT platforms and the relevance of Indonesia’s legal policies with Spotify's policies. Spotify complies with UUHC through mechanisms such as the removal of infringing content, blocking user access, and implementing royalty policies involving Collective Management Organizations (LMK). These policies ensure fair compensation for creators and align with Indonesian regulations, reflecting a commitment to copyright protection and supporting creativity in the digital age.